Fuzzy feedback linearizing controller and its equivalence with the fuzzy nonlinear internal model control structure - Boukezzoula, Reda; Galichet, Sylvie; Foulloy, Laurent (Zielona Góra: Uniwersytet Zielonogórski)
This paper examines the inverse control problem of nonlinear systems with stable dynamics using a fuzzy modeling approach. Indeed, based on the ability of fuzzy systems to approximate any nonlinear mapping, the nonlinear system is represented by a Takagi-Sugeno (TS) fuzzy system, which is then inverted for designing a fuzzy controller.
Keywords: fuzzy control; inverse control; feedback linearization; internal model control